Technology of pastry products for healthy nutrition purposes - Zavadynska Olena (Traektoriâ Nauki, 2016)
The article considers the possibility of using the carrot puree and oil from pumpkin seeds in the preparation of pastry product. Production technology and regulatory documentation for pastry products were developed and nutritional value of products was investigated.